2005
DOI: 10.1007/s00296-005-0080-5
|View full text |Cite
|
Sign up to set email alerts
|

Familial Mediterranean fever and ankylosing spondylitis in a patient with juvenile idiopathic arthritis: a case report and review of the literature

Abstract: The association of familial Mediterranean fever (FMF) with juvenile idiopathic arthritis (JIA) or ankylosing spondylitis (AS), most commonly with negative HLA-B27 antigen, was described in several previous reports, although the pathogenic mechanism of this association still remains unknown. Herein we report an uncommon association of FMF with HLA-B27 positive AS as an occasional coincidence in a patient who had been diagnosed as having JIA 23 years previously.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…The only exception was homozygosity for the M694V MEFV mutation, which compared to the other genotypes, negatively affected the EDSS, destining patients to a more progressive course of their MS. Indeed, the M694V mutation is regarded the most severe mutation in FMF, and carriage of the M694V mutation features many other FMF associations, such as protracted febrile myalgia [30], spondylarthropathy [31], Henoch-Scho¨nlein purpura [32], Behc¸et disease [33], and polyarteritis nodosa [34]. Moreover, Shinar et al [6] studied the role of MEFV mutations in MS, and found that non-Ashkenazi MS patients, carrying a mutated MEFV gene, particularly M694V, express rapid progression to disability.…”
Section: Discussionmentioning
confidence: 99%
“…The only exception was homozygosity for the M694V MEFV mutation, which compared to the other genotypes, negatively affected the EDSS, destining patients to a more progressive course of their MS. Indeed, the M694V mutation is regarded the most severe mutation in FMF, and carriage of the M694V mutation features many other FMF associations, such as protracted febrile myalgia [30], spondylarthropathy [31], Henoch-Scho¨nlein purpura [32], Behc¸et disease [33], and polyarteritis nodosa [34]. Moreover, Shinar et al [6] studied the role of MEFV mutations in MS, and found that non-Ashkenazi MS patients, carrying a mutated MEFV gene, particularly M694V, express rapid progression to disability.…”
Section: Discussionmentioning
confidence: 99%
“…They tested negative for HLA-B27. There were only three HLA-B27-positive cases, with no or minimal spinal changes (eg, squaring of the vertebrae) in the lumbar spine [31][32][33]. MEFV gene mutations were analyzed in 15 patients.…”
Section: Sacroiliitis Associated With Familial Mediterranean Fevermentioning
confidence: 99%
“…[5] Patients who are positive for HLA-B27 and who have spinal ankylosis are considered to have FMF that coincides with AS. [25,26] We found that 34.5% of our cases had spondylitis, but only one of these patients tested positive for HLA-B27. Therefore, this patient was considered to have both FMF and AS.…”
Section: Discussionmentioning
confidence: 82%